Serum MMP-9: a novel biomarker for prediction of clinical relapse in patients with quiescent Crohn’s disease, a analysis - Doron Yablecovitch; Uri Kopylov; Adi Lahat; Michal M. Amitai; Eyal Klang; Dana Ben-Ami Shor; Sandra Neuman; Nina Levhar; Ella Fudim; Benjamin Avidan; Ido Laish; Limor Selinger; et al. (Therapeutic Advances in Gastroenterology, 2019)
Background: Matrix metalloproteinase-9 (MMP-9) is a novel marker of intestinal inflammation. The aim of this study was to assess if serum MMP-9 levels predict clinical flare in patients with quiescent Crohn’s disease (CD). Methods: This study was a post hoc analysis of a prospective observational study in which quiescent CD patients were included and followed until clinical relapse or the end of a 2-year follow-up period. Serial C-reactive protein (CRP) and fecal calprotectin (FC) levels were measured, and the patients underwent repeated capsule endoscopies (CEs) every 6 months. Small bowel inflammation was quantified by Lewis score (LS) for CE. A baseline magnetic resonance enterography was also performed, and MaRIA score was calculated. Serum MMP-9 levels in baseline blood samples were quantified by ELISA. Results: Out of 58 eligible enrolled patients, 16 had a flare. Higher levels of baseline MMP-9 were found in patients who developed subsequent symptomatic flare compared with patients who did not [median 661 ng/ml, 25–75 interquartile range (IQR; 478.2–1441.3) versus 525.5 ng/ ml (339–662.7), respectively, p  = 0.01]. Patients with serum MMP-9 levels of 945 ng/ ml or higher were at increased risk for relapse within 24 months [area under the curve (AUC) of 0.72 [95% confidence interval (CI): 0.56–0.88]; hazard ratio 8.1 (95% CI 3.0–21.9, p  < 0.001)]. Serum MMP-9 concentrations showed weak and moderate correlation to baseline LS and FC, respectively ( r  = 0.31, p  = 0.02; r  = 0.46, p  < 0.001). No correlation was found between serum MMP-9 to CRP and MaRIA score. Conclusions: Serum MMP-9 may be a promising biomarker for prediction of clinical flare in CD patients with quiescent disease.